2022
DOI: 10.3390/polym14163325
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Sustainable Jatropha Oil Bio-Based Polymer Membranes as Alternatives for Environmental Remediation

Abstract: This study aimed to optimize the removal of Cu(II) ions from an aqueous solution using a Jatropha oil bio-based membrane blended with 0.50 wt% graphene oxide (JPU/GO 0.50 wt%) using a central composite model (CCD) design using response surface methodology. The input factors were the feed concentration (60–140) ppm, pressure (1.5–2.5) bar, and solution pH value (3–5). An optimum Cu(II) ions removal of 87% was predicted at 116 ppm feed concentration, 1.5 bar pressure, and pH 3.7, while the validated experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Some interaction terms are insignificant. Harun et al [24] implemented backward elimination method to remove statistically non-significant terms and develop an accurate DOE model; however, this method has not been implemented in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Some interaction terms are insignificant. Harun et al [24] implemented backward elimination method to remove statistically non-significant terms and develop an accurate DOE model; however, this method has not been implemented in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…There are also other research works on surface modifications of polyurethane using various chemical moieties and nanomaterials for enhanced oil absorption reported [ 68 , 69 , 70 , 71 , 72 , 73 ]. There are several recent research works reported in the development of polymer foams for oil–water separations, which elucidates the potential of these foams as promising agents for removing oil from water bodies [ 74 , 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%